Otonomi dan Pembangunan Daerah; Sebuah Kajian Teoritis - Zaenal Arifin; Nuno Guil Hermino Pacheco Magno (Advokasi Hukum & Demokrasi (AHD), 2024)
Regional development and autonomy is two achievement today. The aim and effort of development can be realized well, it is necessarily needed that regional development also endeavor to develop and strengthening regional government. Most important development element to rise regional autonomy, that is institutional capacity and preparation of manpower provided espedially apparatuses of regional government and local finance to exploit income recources of own region. Enchaneement of institutional structure of regional government is necessarily implemented trought: (I) development of structure and functional position, (II) ranking of carrier and duty which is needed and (III) simplication of government for relationship of development in region strata I and II. The other viewpoint, grassroots democracy will rise when democracy is supported by hearted participation of people and based on consciousness of right and obligation as citizen of a state in Unity which favorably enchancement of own initiative and knowing national diversity.